Studi Pendahuluan Pengolahan Air Payau Menjadi Air Bersih Dengan Metode Kombinasi Elektrokoagulasi Dan Adsorpsi Menggunakan Karbosil - Eny Heriani R.N.; Wasinton Simanjuntak; Ilim Ilim (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
This study was carried out to investigate treatment of brackish water using a combination of electrocoagulation and adsorption using carbosil prepared from rice husk with pyrolysis method. Electrocoagulation was applied with the aim to remove natural organic matter in the sample, using aluminim as electrodes, with the particular purpose to study the effect of potenstials. For this purpose, electrocoagulation experiments were conducted at potential of 4, 6, and 8 volt at fixed contact time of 60 minutes. The performance of the method was defined in term of absorbance reduction at the wavelengths of 254 and 285 nm, since the absorbance at these two wave lenghts was found to correlate well with the amount of organic matter in the water samples. The treated water was then subjected to adsorption process at different contac times of 5. 10, and 15 minutes, and the performance of the process was evaluated in term of electrical conductivity reduction. The results obtained indicate that for electrocoagulation process, the higest reduction of natural organic matter content was achieved using potential of 8 volt, and adsorption porcess of 15 minutes was found to result in reduction of electrical conductivity from 15.13 mS/cm to 10.10 mS/cm. Characterization of the carbosil using SEM/EDX technique revealed that the carbosil has practically homogeneous surface and able to adsorb salt and several other elements from the brackish water. Keywords: adsorption, brackish water, carbosil, electrocoagulation